2018
DOI: 10.3389/fpls.2018.01135
|View full text |Cite
|
Sign up to set email alerts
|

High Performance of Photosynthesis and Osmotic Adjustment Are Associated With Salt Tolerance Ability in Rice Carrying Drought Tolerance QTL: Physiological and Co-expression Network Analysis

Abstract: Understanding specific biological processes involving in salt tolerance mechanisms is important for improving traits conferring tolerance to salinity, one of the most important abiotic stresses in plants. Under drought and salinity stresses, plants share overlapping responsive mechanisms such as physiological changes and activation of signaling molecules, which induce and transmit signals through regulator genes in a regulatory network. In this study, two near isogenic lines of rice carrying chromosome segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 68 publications
3
44
0
Order By: Relevance
“…Severe salt stress caused a greater reduction in photosynthetic gas exchange parameters in the salt-sensitive relative to the salt tolerant cultivars. These findings are consistent with Nounjan et al [27] who reported that protecting the photosynthetic process from damage led to high-performance photosynthesis and thus salt tolerance in rice CSSL lines. Our result showed that strong correlation between SAA and the Pn, Tr, and Gs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Severe salt stress caused a greater reduction in photosynthetic gas exchange parameters in the salt-sensitive relative to the salt tolerant cultivars. These findings are consistent with Nounjan et al [27] who reported that protecting the photosynthetic process from damage led to high-performance photosynthesis and thus salt tolerance in rice CSSL lines. Our result showed that strong correlation between SAA and the Pn, Tr, and Gs.…”
Section: Discussionsupporting
confidence: 93%
“…It was reported that the level of antioxidant enzymes rises when plants are exposed to oxidative stress including salt stress [18,25,26]. Analysis of chlorophyll content and chlorophyll-based parameters are considered as an important way to evaluate the integrity during the photosynthetic process under salt stress, while the high performance of photosynthesis was reported to associate with salt tolerance ability [27,28]. In addition, biosynthesis of osmoprotectants and compatible solutes: e.g., proline and sugar) considered an adaptive role in mediating osmotic adjustment and protecting the sub-cellular structures in salt stressed plants [6].…”
Section: Introductionmentioning
confidence: 99%
“…Few salt-tolerant rice genotypes like Damodar, Cypress, Caffey, Jupiter, and Jazzman [21] showed drought tolerance under the greenhouse conditions. The rice genotypes showing both salt and drought tolerance may be due to similar physiological responses and co-expression of the genes under both stress conditions [22].…”
Section: Discussionmentioning
confidence: 99%
“…A vast amount of literature addressing the salt stress response in plant has been published [ 2 ]. Recently, some molecular players involved in mechanisms of salt tolerance have been unveiled in several plant species [ 6 , 7 ], including rice [ 8 , 9 , 10 ]. Despite these efforts, however, few fundamental findings have been successfully applied to crop plants [ 11 ].…”
Section: Introductionmentioning
confidence: 99%